Submucosal angiogenesis in traction-induced esophageal lengthening for long-gap esophageal atresia: A case report - Parker T. Evans; Laura Stafman; Hernan Correa; Maren Shipe; Harold Lovvorn, III; Jamie Robinson (Journal of Pediatric Surgery Case Reports, 2024)
Introduction: Traction-induced growth (Foker procedure) is a method for esophageal lengthening when primary anastomosis is not feasible in long-gap type A esophageal atresia (EA). We sought to identify the source of esophageal vascularization after thoracoscopic internal traction by analyzing markers of angiogenesis in resected esophageal pouch tips. Case report: A child with Type A EA underwent esophageal lengthening with internal traction. In addition to EA, the patient also had trisomy 21, duodenal atresia, intestinal malrotation, and congenital heart disease. Operations for EA included thoracoscopic esophageal traction system placement at 7 months of age, and 5 subsequent tightening procedures over the following month. Baseline esophageal gap length was 5.5 cm without tension and 4 cm at maximal tension. Gap length was 3.6 cm, 1.4 cm, 1.3 cm, 7 mm, and 5 mm after each tightening procedure, respectively. Final esophageal anastomosis was done at 8 months of age. At the time of the anastomosis, angiogenic vessels were grossly visible at the ends of each esophageal pouch and indocyanine green fluorescence angiography demonstrated vascularization. Resected samples of the esophageal pouches were analyzed with immunohistochemistry for expression of ERG, a marker of angiogenesis. The patient who underwent traction demonstrated increased submucosal ERG expression (average 6.30 % cells) compared to 5 control patients who did not require traction-based lengthening to achieve anastomosis (average 1.34 % cells). Conclusion: Thoracoscopic traction with serial tightening achieves adequate growth to restore esophageal continuity in patients with long-gap EA. Our findings suggest that anastomotic blood supply relies upon submucosal angiogenesis.